Satellite laser ranging at ultra-high PRF of hundreds of kilohertz all day - Long, Mingliang; Zhang, Haifeng; Yu, Rong Zong; Wu, Zhibo; Qin, Si; Zhang, Zhongping (Frontiers in Physics, 2022)
Satellite laser ranging (SLR) had been operated at a pulse repetition frequency (PRF) from ∼10 Hz to 10 kHz; the ultra-high PRF of SLR (UH-SLR) is a trend of development. In this study, an alternate working mode of laser firing and gated pulse bursts is proposed to solve the problem of laser echo interference by laser backscattering. Through an ultra-high PRF of 200-kHz picosecond green laser with single-pulse energy of 80 μJ and a pulse width of 10 ps and a ranging gate device, UH-SLR has been built by an aperture of the 60-cm SLR system in the Shanghai Astronomical Observatory. By this UH-SLR, low-orbit to high-orbit and geostationary orbit satellites are measured night and day and also for low-orbit and medium-orbit satellites in the daytime. The normal point (NP) accuracy is ∼30 μm for low-orbit satellites and ∼100 μm for high-orbit satellites, which provides an effective method for the development of ultra-high PRF and high-precision space target laser ranging.